2004
DOI: 10.1073/pnas.0401586101
|View full text |Cite
|
Sign up to set email alerts
|

Multiple pathways process stalled replication forks

Abstract: Impairment of replication fork progression is a serious threat to living organisms and a potential source of genome instability. Studies in prokaryotes have provided evidence that inactivated replication forks can restart by the reassembly of the replication machinery. Several strategies for the processing of inactivated replication forks before replisome reassembly have been described. Most of these require the action of recombination proteins, with different proteins being implicated, depending on the cause … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
330
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 309 publications
(338 citation statements)
references
References 71 publications
5
330
1
2
Order By: Relevance
“…This is consistent with in vitro experiments that have shown UvrD to be capable of removing RecA molecules from DNA thereby disrupting a recombination event (9,18,18,19). It has also been suggested that UvrD could act to resolve the intermediate formed by replication fork regression so that the lesion may be repaired or bypassed immediately (16,20).…”
supporting
confidence: 72%
“…This is consistent with in vitro experiments that have shown UvrD to be capable of removing RecA molecules from DNA thereby disrupting a recombination event (9,18,18,19). It has also been suggested that UvrD could act to resolve the intermediate formed by replication fork regression so that the lesion may be repaired or bypassed immediately (16,20).…”
supporting
confidence: 72%
“…A key intermediate in this type of genomic instability is thought to be the double strand break (DSB), and a large body of evidence now implicates DSB repair defects in cancer susceptibility. In the absence of extrinsic DNA damage, most chromosomal DSBs in cycling cells, and the associated chromosomal rearrangements, are thought to arise during the S phase of the cell cycle as a result of replication across a damaged DNA template [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The DSG has received less attention than its illustrious cousin, the DSB, but recent work in model organisms has reawakened interest in the DSG as a potential intermediate in genomic instability and cancer [7]. DSBs and DSGs can be repaired in an error-free manner by sister chromatid recombination (SCR), a mechanism whereby the damaged chromatid uses the intact sister as a template for repair by homologous recombination (HR) [5,8,9]. SCR competes with alternative error-prone pathways for repair of DSBs and DSGs and is therefore an important bulwark against the threats of genomic instability and cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the solid genetic evidence supporting this model, the molecular characterization of HLJs formed in vivo and an estimation of the extent of fork regression are still scarce (11-13). Moreover, replication restart after fork stalling was also suggested to occur by means of mechanisms that do not necessarily need fork reversal (FR) (8,14).…”
mentioning
confidence: 99%